The Cost Implications of Reaching Universal Coverage of Maternity Health Services in Siaya County, Western Kenya - Oluoch, Felix; Ayodo, George; Owino, Fredrick; Okuto, Erick (Public Health Research, 2020)
In Kenya, no studies have attempted to model alternative scenarios of the cost-implications of reaching universal coverage (i.e. 95% population coverage) of the existing maternity health services network at the ward administrative level. A cross-sectional study design used publicly available geospatial data in combination with routine data from the web-based district health information software (DHIS2) platform. AccessMod (version 5) was used for scaling up analysis. ArcGIS (version 10.5) sufficed for the preparation of geospatial input and the mapping of AccessMod results, respectively. The geographic coverage of three alternative scenarios to scale up the existing maternity health services network was tested and compared to the status quo. The findings in Siaya County confirm that even if the existing maternity health services network had unlimited capacity, almost 30% of pregnant women would still not be covered. Moreover, targeting the upgrade of hospital facility types currently working beyond their capacity would offer the best value for every additional resource allocated as compared to targeting either health centers or dispensaries, otherwise reaching universal coverage will require the construction of 32 second-tier facilities in Siaya County, as it is the most equitable approach in terms of physical accessibility to maternity health services. Future research should also consider the Lives Saved Tool (LiST) to model the effect of scaling up the geographic coverage of maternal health interventions on maternal mortality in Siaya County.
Keywords: DHIS2; Geographic information systems; Maternity services; Scaling up analysis; Travelling time; Universal coverage